Мобільна скульптура Мізина: типологія, технологія, художня стилістика - Яковлева, Л.А. (Кам’яна доба України, 2011)
Стаття присвячена детальному аналізу технології, типологіх та стилістики мобільної скульптури Мізина. The total inventory of the ivory statuettes from Mezine is constituted of 18 exemplars which are classified into four types following their morphology and technology. The detailed studies are based on the analysis of the raw material technique of execution, the morphology and the geometric decoration, as well as the stylization of their representation.